Development of Science Student Worksheet Based on Mangrove Environmental Resources to Improve Critical Thinking Skills - Santoso, Didik; Syukur, Abdul; Karnan, Karnan; Japa, Lalu (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Innovation in the learning process needs to be carried out, especially in the development of student worksheets. Mangrove environmental resources can be developed into science learning resources, one of which is student worksheets. This research was conducted to determine the effectiveness of natural resource-based science student worksheet in the mangrove environment to improve the critical thinking skills of Coastal Middle School students in East Lombok Regency. The type of research is development research using a one group pre-test post-test design. The research results showed that the LKPD science based on mangrove environmental resources that was developed was effective in improving the critical thinking skills of West Lombok Coastal Middle School students in the medium category (0.61%). Critical thinking skills indicators 1, 2, and 3 are in the high category while indicators 4 and 5 are in the medium category. In conclusion, the science worksheet based on mangrove environmental resources is effective in improving students' critical thinking skills.